PENDEKATAN SIMULASI UNTUK MENENTUKAN FREKUENSI AMATAN DALAM PENDUGAAN PRODUKTIVITAS CABAI - Wijayanto, Hari (Informatika Pertanian, 2014)
Horticulture is one of the important commodities in the agricultural sector. Methods of horticulture data collection is continuously developed to meet the needs of planning, one of which is a method of counting clump (RC) to estimate the productivity of horticultural commodities. However, the method of the RC is still encountering difficulties in its application, one of the difficulties is in the observation of crops with multiple harverst, such as chili. Simulation was conducted through generating productivity data using 5 models on group productivity data using 5 models on group productivity of plot samples with the same general characteristics. Through the simulation approach, the results of this study indicate that the observations of only partial harvest (twice) can estimate well total observation of harvest, provided the harvest frequency is known.